Use of Digital Learning Technologies in Education on the Example of Smart Education - Jurayev Tuychi Norbutaevich (Newinera Publisher, 2020)
Currently, the main task of teachers is to develop the needs of students for self-development and self-improvement, which is a decisive factor in the upbringing and formation of personality. Practice has shown that modern teachers better assimilate the studied topics as a result of using SMART technologies to effectively determine the goals of the lesson, compared to the indicators of topics studied traditionally. This article discuss about analyzes the methods of using smart learning apps in the classroom and the expected results.